Bulgarian Business, Entrepreneurs, and Managers in the Context of Bulgaria’s Accession to the EU: Challenges and Possible Solutions (UNWE Yearbook, 2005)
Bulgaria’s accession to the EU goes hand in hand with growing opportunities and challenges which confront Bulgarian businesses, entrepreneurs and managers. Solutions should be sought to deal with these challenges. It is becoming increasingly clear that the EU membership has not positive effects alone, but poses problems of increasing complexity for both big size businesses (BB) and (especially) small- and medium-size businesses (SMB). The identification and meeting the challenges of the EU integration for Bulgarian businesses, entrepreneurs and managers is precisely the focus of the present research.Firstly, the paper outlines the summary of the experiences of some of the 10 new EU members (mainly, Poland and Hungary) which serves as a point of departure in the analysis, as well as in the evaluation of the influence of the process of integration in Bulgaria. Secondly, concrete challenges of the EU membership for Bulgarian businesses, entrepreneurs and managers are analyzed. Two principal groups are distinguished: a group related to the problems of management and the conduct of managers and entrepreneurs, and a group involving the introduction and operation of different regulations, standards and practices.The paper lays a special emphasis on the current situation and conduct of Bulgarian businesses, entrepreneurs and managers, with a differentiated analysis according to the inherent specifics of BB-s and SMB-s, ranging from the level of their competitiveness as a whole to individual component processes.Finally, the paper outlines the principal guidelines for the solutions of the identified challenges; branch unions (chambers) and NGOs, as well as the business level (businesses, entrepreneurs, managers). Its argued that one of the greatest weaknesses not only in the context of the EU accession but typical of the Bulgarian economy and society as a whole, is its failure to combine the efforts of different levels and its lack of focus. It is a must to cope with these problems.